Molecular methods for virus detection - Wiedbrauk, Danny L.; Farkas, Daniel H. (Academic Press, 1995)
Molecular diagnostic procedures have been described in a number of recent books and articles. However, these publications have not focused on virus detection, nor have they provided practical protocols for the newer molecular methods. Written by the inventors or principal developers of these technologies, Molecular Methods for Virus Detection provides both reviews of individual methods and instructions for detecting virus nucleic acid sequences in clinical specimens. Each procedure includes quality assurance protocols that are often ignored by other methodology books. Molecular Methods for Virus Detection provides clinically relevant procedures for many of the newer diagnostic methodologies. Key Features * Provides state-of-the-art PCR methods for amplification, quantitation, in situ hybridization, and multiplex reactions * Goes beyond PCR with protocols for 3SR, NASBA, LCR, SDA, and LAT * Covers important virus detection methods such as in situ hybridization; Southern, dot, and slot blots; branched chain signal amplification; and chemiluminescence * Includes quality control information crucial in research and clinical laboratories * Most chapters are written by the inventors and principal developers of the methodologies * Includes color plates, 77 figures, and 18 tables.